Experimental investigation of cyclic response of stainless steel reinforced concrete columns - José Melo (2019)
Corrosion of carbon steel reinforcement is the major cause of premature deterioration of reinforced concrete buildings and infrastructure. There are increasing interests in the use of maintenance-free materials such as stainless steel reinforcement in concrete, with inherent durability and resistance to various forms of corrosion and favourable mechanical properties, in particular excellent ductility and cyclic resistance. This paper presents the main results of an experimental programme designed to investigate the potential benefits of the relatively high ductility and substantial strain hardening of stainless steel on the cyclic performance of reinforced concrete columns with stainless steel reinforcing bars. Three experimental tests were performed on full-scale columns, two with duplex EN 1.4462 stainless steel reinforcement, one tested under cyclic lateral loading and one tested monotonically, and one control specimen with A500 carbon steel reinforcement tested under cyclic lateral loading. In addition, conventional pull-out tests and tensile tests were conducted for a comparative assessment of the bond and mechanical properties of the reinforcement bars. The force-displacement global response and the dissipated energy evolution of the tested columns are presented and discussed.